Repellent and Metamorphosis Capability of Alphitobius diaperinus Exposed to Gamal Leaf Extracts - Wibowo Fatria Fadillah Nur; Priyantini Widiyaningrum (Jurnal Ilmu Pertanian Indonesia, 2025)
Alphitobius diaperinus is an insect pest that is difficult to control in conventional chicken farms. In high populations, this insect can damage the infrastructure of the coop, disrupt chicken feeding activities, and is a known vector of pathogens. Currently, the control of A. diaperinus still relies on synthetic insecticides that have been proven to be resistant to target pests, toxic to non-target organisms, and pollute the environment. This study aimed to analyze the potential of gamal (Gliricidia sepium) leaf extract as a bioinsecticide in terms of repellency response and its effect on the metamorphosis of A. diaperinus. The repellency response was measured through a preference test using a Y-olfactometer at 6 concentration levels, whereas metamorphosis ability was tested at 6 sub-lethal concentrations. Each treatment was performed in 5 replications. The repellency response was descriptively analyzed based on the repellency percentage (PP) and preference index (IP) values. The metamorphosis ability test results were analyzed using non-parametric Kruskal-Wallis and Mann-Whitney U tests. The results showed that all treatments had PP values > 80% with negative IP. The results of the Kruskal-Wallis test showed significant differences in the extract concentrations between the treatment groups (asymp. sig < 0.05). A higher extract concentration caused a decrease in the number of larvae that successfully became imagoes. In conclusion, A. diaperinus showed a high repellency response to gamal leaf extract, and the gamal leaf extract had a strong repellent effect. The extract concentration also affected the metamorphosis of A. diaperinus larvae. Keywords: Alphitobius diaperinus, bioinsecticide, Gliricidia sepium, Metamorphosis, Repellency response